PENGGUNAAN METODE TUTOR SEBAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG TEKS CERPEN PADA SISWA KELAS IX B SMP NEGERI 2 MODO - FATHONI, ACHMAD (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2023)
The purpose of this research is (1) to determine the improvement in learning outcomes of class IX B students at SMP Negeri 2 Modo Semester 1 of the 2023/2024 academic year after using the peer tutoring method. (2) want to know the increase in learning motivation of class IX B students at SMP Negeri 2 Modo Semester 1 of the 2023/2024 academic year after using the peer tutoring method. This research uses action research in two cycles, each cycle consisting of four stages, namely planning, activities, observation and reflection. The target of this research is class IX B students of SMP Negeri 2 Modo for the 2023/2024 academic year. The conclusion that can be drawn in this research is that the use of the peer tutoring method for class IX B students of SMP Negeri 2 Modo Semester 1 of the 2023/2024 academic year has a positive impact in improving student learning outcomes regarding short story texts which is characterized by increasing student learning completeness (classical) in the cycle. I there were 14 students (70%) and in cycle II there were 19 students (95%) out of 20 students. Therefore, this method is suitable for use in Indonesian language subjects, especially about finding the intrinsic elements of short stories. ABSTRAKTujuan penelitian ini adalah (1) ingin mengetahui peningkatan hasil belajar siswa kelas IX B SMP Negeri 2 Modo Semester 1 Tahun Pelajaran 2023/2024 setelah menggunakan metode tutor sebaya. (2) ingin mengetahui peningkatan motivasi belajar siswa kelas IX B SMP Negeri 2 Modo Semester 1 Tahun Pelajaran 2023/2024 setelah menggunakan metode tutor sebaya. Penelitian ini menggunakan penelitian tindakan (action research) sebanyak dua siklus yang setiap siklusnya terdiri atas empat tahap yaitu perencanaan, kegiatan, pengamatan, dan refleksi. Sasaran penelitian ini adalah siswa kelas IX B SMP Negeri 2 Modo Tahun Pelajaran 2023/2024. Kesimpulan yang dapat ditarik dalam penelitian ini adalah penggunaan metode tutor sebaya siswa kelas IX B SMP Negeri 2 Modo Semester 1 Tahun Pelajaran 2023/2024 memiliki dampak positif dalam meningkatkan hasil belajar siswa tentang teks cerpen yang ditandai dengan peningkatan ketuntasan belajar siswa (klasikal) pada siklus I sebanyak 14 siswa ( 70%) dan pada siklus II terdapat 19 siswa ( 95%) dari 20 siswa. Oleh karena itu, metode ini cocok digunakan pada mata pelajaran Bahasa Indonesia khususnya tentang menemukan unsur intrinsik cerpen.